Improving Students’ Thinking Skill Based on Class Interaction in Discovery Instructional: A Case of Lesson Study - Widoretno, S.; Dwiastuti, S. (Jurnal Pendidikan IPA Indonesia, 2019)
Lesson Study (LS) activity aims to improve teachers’ professionalism using discovery-based instructional design. Teachers’ professionalism was measured based on communication during the learning process, especially questions and statements from the teachers and students on various topics. Thirty-two high school biology teachers and twelve model teachers involved in this research. The procedures of the LS activity included curriculum review (up to constructing learning objectives); lesson plan making; implementation of lesson plans; communication of the results; and workshop. The research showed that LS activity changed the questioning skills of the teachers and students. Changes in the quality of teachers’ questions and statements were proportionate with the changes in students’ answers quality. The quality of questions and statements affected the teachers’ competencies; also, improved the quality of learning as it facilitated students’ thinking of learning as thinking categories.